Insectivory in Potamotrygon signata (Chondrichthyes: Potamotrygonidae), an endemic freshwater stingray from the Parnaíba River basin, northeastern Brazil - Moro, G.; Charvet, P.; Rosa, RS (Brazilian journal of biology, 2012)
Potamotrygon signata is an endemic freshwater stingray species in the Parnaíba River basin, Brazil. After its original description, only citations in systematic lists were recorded in the literature and the biology of the species remains unknown, including the feeding habits. The aim of this study is to characterize the overall diet of P. signata based on analysing stomach contents and to provide preliminary information on intraspecific diet variability between sexes and maturity stages. The stomach contents of 56 specimens of P. signata were analyzed. The taxonomic identification of food items showed the presence of 13 prey orders, including insects, mollusks, crustaceans and teleost fish. The Index of Relative Importance (IRI%) indicated P. signata as an insectivorous species, with a dominance of Diptera larvae (60.64%) and Ephemeroptera nymphs (34.68%). Differences in diet were observed between sexes, as well as between mature and immature individuals. The IRI% of females showed a similar occurrence of Diptera and Ephemeroptera (47.12% and 47.86%, respectively), whereas for males, Ephemeroptera was the main item (79.56%). Immature individuals showed a dominance of Diptera (76.20%) while mature individuals showed a similar occurrence of Diptera (46.95%) and Ephemeroptera (47.23%). The observed sexual and ontogenetic differences in diet may be related to distinct nutritional requirements of males and females, and to the variation of morphological aspects of the oral apparatus and dentition of males and females and of immature individuals and adults. The essentially insectivorous diet of the species is possibly adaptively advantageous in the Caatinga semi-arid environment, where the availability of fish as prey may be subject to strong seasonal variation. Potamotrygon signata é uma espécie de raia de água doce endêmica da bacia do rio Parnaíba, Brasil. Após a sua descrição original, apenas citações em listas sistemáticas foram registradas na literatura e a biologia da espécie permanece desconhecida, incluindo os hábitos alimentares. Este estudo teve como objetivo caracterizar a dieta de P. signata com base na análise do conteúdo estomacal, e fornecer informações preliminares sobre a variabilidade intraespecífica da dieta entre os sexos e segundo os estádios de maturidade. O conteúdo estomacal de 56 espécimes de P. signata foi analisado. A identificação taxonômica dos itens alimentares revelou a presença de 13 ordens de presas, incluindo insetos, moluscos, crustáceos e peixes teleósteos. O Índice de Importância Relativa (IRI%) indicou P. signata como uma espécie insetívora, com predominância de larvas de Diptera (60.64%) e ninfas de Ephemeroptera (34.68%). Diferenças na dieta entre os sexos foram observadas, bem como entre os indivíduos maduros e imaturos. A IRI% das fêmeas mostrou uma ocorrência similar de Diptera e Ephemeroptera (47.12% e 47.86%, respectivamente), enquanto para os machos, Ephemeroptera foi o principal item (79.56%). Indivíduos imaturos mostraram um predomínio de Diptera (76.20%), enquanto indivíduos maduros apresentaram uma ocorrência similar de Diptera (46.95%) e Ephemeroptera (47.23%). As diferenças sexuais e ontogenéticas observadas na dieta podem estar relacionadas a diferentes necessidades nutricionais de machos e fêmeas, e à variação de aspectos morfológicos do aparelho bucal e dentição de machos e fêmeas e de indivíduos imaturos e maduros. A dieta essencialmente insetívora desta espécie possivelmente é uma vantagem adaptativa para esta espécie no ambiente semiárido da Caatinga, onde a disponibilidade de peixes como presa pode sofrer grandes variações sazonais.